1992
DOI: 10.1111/j.1469-185x.1992.tb01189.x
|View full text |Cite
|
Sign up to set email alerts
|

The Control of Sexual Morphogenesis in the Ascomycotina

Abstract: Summary (1) A series of factors controls sexual morphogenesis in the Ascomycotina, a process involving the formation of novel structures such as ascocarps (fruit bodies) and asci (sacs containing spores) during sexual reproduction. (2) Environmental and genetic factors must be correct before Ascomycetes may sexually reproduce. Compatibility in many heterothallic species is under polygenic control, with the mating type loci and also other genetic factors determining the productivity of sexual crosses. (3) Class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 219 publications
1
32
0
1
Order By: Relevance
“…This process needs molecular communication between mating partners, followed by finely organized morphogenetic changes, regulated by a number of genes that are affected by either intrinsic and/or environmental stimuli, like age of the culture, temperature, nutrient status or light. Early studies (Dyer et al 1992) suggested that sexual morphogenesis in fungi is under polygenic control and several genes involved in sexual communication have already been characterized in detail (Shen et al 1999;Vallim et al 2000; Pö ggeler and Kü ck 2001; Kim et al 2002;Turina et al 2003;Kim and Borkovich 2004). Nevertheless the molecular mechanisms of this series of events are still not fully understood (Coppin et al 1997;Kronstadt and Staben 1997;Shiu and Glass 2000;Trail et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This process needs molecular communication between mating partners, followed by finely organized morphogenetic changes, regulated by a number of genes that are affected by either intrinsic and/or environmental stimuli, like age of the culture, temperature, nutrient status or light. Early studies (Dyer et al 1992) suggested that sexual morphogenesis in fungi is under polygenic control and several genes involved in sexual communication have already been characterized in detail (Shen et al 1999;Vallim et al 2000; Pö ggeler and Kü ck 2001; Kim et al 2002;Turina et al 2003;Kim and Borkovich 2004). Nevertheless the molecular mechanisms of this series of events are still not fully understood (Coppin et al 1997;Kronstadt and Staben 1997;Shiu and Glass 2000;Trail et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…These may be designated MAT-1 and MAT-2, A and a, or plus "ϩ" and minus "Ϫ" (Dyer et al, 1992). Compatibility is governed by the presence of mating-type genes and progress has been made in cloning these genes from certain ascomycete species.…”
Section: Accepted For Publication May 1 2001mentioning
confidence: 99%
“…It has been proposed that the incompatibility reaction may limit the spread of harmful cytoplasmic or nuclear elements (Caten, 1972), and prevent resource plundering (Debets & Griffiths, 1998). It has also been suggested that vegetative incompatibility may promote the initiation of sexual reproduction in some species as a result of non-self recognition (Dyer et al, 1992). Individuals that share the same heterokaryon or vegetative incompatibility loci can fuse to form a heterokaryon and are then considered to belong to the same vegetative compatible group (Glass et al, 2000).…”
Section: Introductionmentioning
confidence: 99%